Registration of natural emission of hydrocarbon deposits on the basis of two-frequency signals - Yanushkevich Viktar; Dauhiala Dzmitry; Burachonak Iryna; Dauhiala Natallia; Abramenka Siarhei (E3S Web of Conferences)
The article presents the results of modelling and experimental studies on the method of registration of natural emission of hydrocarbon deposits on the basis of two-frequency signals. The application of natural emission registration of hydrocarbons for accuracy increase of electromagnetic methods is substantiated. The dispersion dependences of the combination terms of the tensor of the geological environment over hydrocarbons are analyzed in a wide range of frequencies of the signals used. The frequencies of electron cyclotron resonance and electron plasma resonance have been determined, that allow to distinguish hydrocarbon deposits against the background of other objects. The results of field measurements of the proposed method at Vostochno-Drozdovskoye oil field and Osipovichy gas storage facility are given. The application of multiple illumination frequencies is proposed to improve the information capability of the search methods and the accuracy of hydrocarbon boundary determination.